Desain Berdasarkan Riset Penataan Permukiman Kumuh Di Kelurahan Pesisir Kecamatan Lima Puluh kota Pekanbaru - Manao, Gihon Juang Sataro; Amanati, Ratna; Aldy, Pedia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Kelurahan Pesisir is one of the slums area located on the banks of the Siak River Pekanbaru. Design by research aims to find design solutions for the problems of slums with using an assessment of a region through character activities. The form of design solutions forregulation slums related to the five elements of the image of the city; i.e. paths, edges, nodes, districts, and landmarks. The five elements explain image of area obtained from local residents.The issue gained that the region is well-known as the ports of goods and shops citizens who make road traffic in the area becomes crowded. So, the design of the slum settlements to be beneficial to the community activities. That requires a walkway for the carts and pedestrians crossing roads and rivers in the area without disturbing the road traffic.Keyword: Research, Regulation, Settlement, Slum.